Pengembangan Media Pembelajaran IPAS Ludo Game sebagai Upaya Meningkatkan Hasil Belajar Siswa Kelas III Sekolah Dasar - Aurora, Ainnur Ratri; Isdaryanti, Barokah (Paedagogie, 2026)
This research was conducted with the aim of developing a science learning media in the form of a Ludo Game that raises the topic of natural and artificial phenomena, while also assessing its feasibility and effectiveness in improving the learning outcomes of third-grade elementary school students. The method applied was Research and Development (R&D) with the ADDIE development model that includes five stages, namely analysis, design, development, implementation, and evaluation. Data were obtained through validation questionnaires from media experts and material experts, teacher and student response questionnaires, and learning outcome tests in the form of pretests and posttests. Data analysis was carried out through product feasibility tests, Shapiro Wilk normality tests, paired sample t-tests, and N-Gain calculations using SPSS version 25. The results showed that the media was 93% feasibility from media experts and 85% from material experts with a very feasible category. The t-test obtained a significance of 0.000 (<0.05) and an average N-Gain value of 0.3310 and 0.3406 in the moderate category. Thus, the media was declared feasible and effective in improving student learning outcomes.